Pregnancy-Specific Concerns and Psychological Impact of COVID-19 on Antenatal Women - Singh, Sanjay; Nair, Vinod G; Singh, Virendra Vikram; Tiwari, Shyamji; Arora, Devendra; Dey, Madhusudan; Tiwari, Ravindu; Nair, Sreeni V (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: The ongoing COVID-19 pandemic is causing widespread concern, fear, stress, anxiety, and depression throughout the population worldwide. Pregnant women, being a vulnerable group, are grossly affected by these changing environmental scenarios. The spread of Corona Virus infection itself and the subsequent nation-wide lockdown in India, just like many other countries, has caused a serious impact on antenatal patients. The objective of this study was to bring out the specific concerns of pregnant women during the ongoing COVID-19 pandemic and also to assess the prevalence of Depression and Anxiety Disorder owing to the pandemic. STUDY DESIGN: This cross-sectional survey among antenatal patients was conducted in the outpatient department of a tertiary care obstetric center which is also a designated COVID hospital. Prevalidated questionnaires, Personal Health Questionnaire-9 & Generalized Anxiety Disorder questionnaire-7 were used for data collection. A semi-structured questionnaire was used to evaluate pregnancy-specific concerns of the patients with respect to the COVID-19 pandemic. RESULTS: The overall prevalence of moderate to severe depression in the survey was found to be 13.2% (n=66). The prevalence of moderate to severe anxiety disorder was found to be 9.8% (n=49). CONCLUSION: This study has brought out the need for urgent attention to the psychological impact of COVID-19 on pregnant women. Pregnant women being a vulnerable group, especially during this pandemic, need special attention to their psychological wellbeing as well.